LANGUAGE VARIETIES IN GRIME VALLEY JAYAPURA Regional Dialectological Study - FAUTNGIL, CHRIST; Meko Mbete, Prof. Dr. Aron; Lauder, M.A., Prof. Dr. Multamia; Dhanawaty, M.S., Dr. Ni Made (e-Journal of Linguistics; Vol. 3. 1 Januari 2009 No. 1)
A regional dialectological study is a research of mapping languages in anarea, as what conducted in this study in Grime Valley Jayapura. This research isbased on the theory of traditional dialectology currently known as a theory havingnormative rules to determine the status of a variety as a language, dialect, subdialect,difference in speaking and no difference in speaking, both in the valleyand outside the valley.The two language aspects employed as indicators are sound and lexicalaspects. What is discussed from these two aspects is variation. In terms of soundaspect, discussion of variation covers sound description, correspondence, andcalculation of sound distance from dialectometrie, phoneme inventory, andphoneme distribution. In terms of lexical aspect, lexical distribution andcalculation of vocabulary distance from lexical dialectometrie are discussed. Afterthat, varieties are classified, groupings of phonological and lexical varieties arecompared, and the status of every variety, as a language, a dialect, sub-dialect andso on is identified.Phonological study shows variation in correspondence aspect, calculationof sound distance, inventory, and phoneme distribution. Correspondence hasvarious variations such as the existence of irregular sound which is unpredictableon each point of observation. Calculation of sound distance shows a difference,but the difference is limited to the point in which there is no difference inspeaking. The inventory and distribution contain differences in number, type andexistence of given phonemes.Lexical study shows varied distribution at the middle and outskirts of theValley. The calculation of vocabulary distance shows that there is no difference inlanguage. Groupings of phonological and lexical varieties are different in numberbut identical in the points of observation. If identified in terms of language anddialect for the four varieties, namely Nimboran, Gresi, Kwansu and Kemtuk, itturns out that there are differences in language, that is, Nimboran, Kwansu andKemtuk Gresi. In the previous studies, Kemtuk and Gresi were known as twolanguages, but in this calculation, the difference was in the level of dialect.Further study need to be conducted to investigate the relation of languages inGrime Valley with those in the surrounding areas. It is also necessary to conduct adiachronic research and to apply other theories.2
Keywords: varieties, phonology and lexical, language and dialect.